2016
DOI: 10.1371/journal.pmed.1002169
|View full text |Cite
|
Sign up to set email alerts
|

Under-prescribing of Prevention Drugs and Primary Prevention of Stroke and Transient Ischaemic Attack in UK General Practice: A Retrospective Analysis

Abstract: BackgroundStroke is a leading cause of death and disability; worldwide it is estimated that 16.9 million people have a first stroke each year. Lipid-lowering, anticoagulant, and antihypertensive drugs can prevent strokes, but may be underused.Methods and FindingsWe analysed anonymised electronic primary care records from a United Kingdom (UK) primary care database that covers approximately 6% of the UK population. Patients with first-ever stroke/transient ischaemic attack (TIA), ≥18 y, with diagnosis between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…This phenomenon may be explained due to the intention of doctors to prescribe less aggressive therapies to patients who, due to their conditions and comorbidities, are more likely to present with problems related to these medications . However, said patients could benefit from an adequate prescription . The use of ACEI or an ARB‐II was related with a lower probability of presenting a PPO, considering that these medications are one of the fundamental bases in the treatment of various cardiovascular diseases (including hypertension, HF and IHD) and their use impacts several START criteria …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This phenomenon may be explained due to the intention of doctors to prescribe less aggressive therapies to patients who, due to their conditions and comorbidities, are more likely to present with problems related to these medications . However, said patients could benefit from an adequate prescription . The use of ACEI or an ARB‐II was related with a lower probability of presenting a PPO, considering that these medications are one of the fundamental bases in the treatment of various cardiovascular diseases (including hypertension, HF and IHD) and their use impacts several START criteria …”
Section: Discussionmentioning
confidence: 99%
“…23,36 However, said patients could benefit from an adequate prescription. 11 The use of ACEI or an ARB-II was related with a lower probability of presenting a PPO, considering that these medications are one of the fundamental bases in the treatment of various cardiovascular diseases (including hypertension, HF and IHD) and their use impacts several START criteria. 4 This study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although controlled clinical studies proved the efficacy of primary prevention with statins in reducing all-cause mortality and the risk of primary cardiovascular events [30,31], other observational studies also reported the undertreatment of patients eligible for preventive lipid-lowering therapy [27,[32][33][34][35][36]. The rates of undertreatment with antihypertensive agents are lower [36][37][38], which can be explained by well-established evidence on efficacy, good safety profiles and the low cost of these drugs [37]. Meanwhile, some controversy regarding the risks and benefits of statins used in primary prevention still exists both in scientific literature [39] and clinical practice.…”
Section: Discussionmentioning
confidence: 99%